Ocular immune privilege - Taylor, AW (Eye (Lond), 2009)
It has been over 60 years since the phrase immune privilege was used by Sir Peter Medawar to describe the lack of an immune response against allografts placed into the ocular microenvironment. Since then, we have come to understand that the mechanisms of ocular immune privilege include unique anatomical features of a blood barrier and a lack of direct lymphatic drainage. Also, we know that the ocular microenvironment is rich with immunosuppressive molecules that influence the activity of immune cells. Moreover, the placement of foreign antigen into the ocular microenvironment can induce a systemic form of tolerance to the foreign antigen called anterior chamber-associated immune deviation (ACAID). Many soluble immunomodulators are found in aqueous humour, and are a mixture of growth factors, cytokines, neuropeptides, and soluble receptors. This is a continuously growing list. The mechanisms of ocular immune privilege induce apoptosis, promote the production of anti-inflammatory cytokines, and mediate the activation of antigen-specific regulatory immunity. These mechanisms of immune privilege also attempt to impose themselves upon immunity within the uveitic eye. The adaptation of several anatomical and biochemical mechanisms to establish an immune privileged microenvironment within the eye makes the eye immunologically unique. It is a tissue site where we may learn how immunity is regulated in inflammation and at rest. Success in translating the lessons of ocular immune privilege to other tissues has the potential to drastically change the therapy and clinical outcomes of autoimmune diseases and allograft survival.